Some typical features of homo virtualis in the virtualized informational society - Mariyko, Svitlana (Actual Problems of Mind, 2017)
The author attempts by employing a mask-theory to explicate some typical features and characteristics of homo virtualis as a phenomenon of virtualized informational society. One finds among these features the configurative identity, the change in the status of human body, the distance from the real social roles, activity, pseudo-publicity and specific word-view.